Acupuncture combined with herbal medicine versus herbal medicine alone for plaque psoriasis: a systematic review protocol - Xiao, Shiju (Ann Transl Med, 2019)
BACKGROUND: Psoriasis is a condition with a multifactorial etiopathogenesis worldwide, and plaque psoriasis, which is characterized by redness, thickness, and scaling, is the most common kind. Individuals living with psoriasis show low levels of life quality, and having fewer or less extensive lesions may improve spiritual and mental health. Therefore, our objective is to explore the effectiveness of acupuncture combined with herbal medicine for plaque psoriasis and to compare acupuncture combined with herbal medicine with herbal medicine alone. METHODS: Databases including PubMed, MEDLINE, the Cochrane Library, Excerpta Medica (EMBASE), the Chinese Biomedical Literature Database (CBM), the China National Knowledge Infrastructure Database (CNKI), the Wanfang database and the Chinese Scientific Journal Database (VIP database) will be searched from inception to March 2018. We will employ hand searches, and grey literature will also be obtained. Only randomized controlled trials evaluating acupuncture combined with herbal medicine to treat plaque psoriasis in adults will be assessed. The Psoriasis Area and Severity Index score (PASI score), the itching index, the life quality scores, and the anxiety index will be the outcome measures. Two independent reviewers will select the articles included, assess the risk of bias and extract data according to the inclusion criteria. A third reviewer will resolve disagreements. The purpose of this study will be to identify the effect of acupuncture combined with herbal medicine on the lesions (PASI score), symptoms (itching index, life quality scores) and mental status (anxiety index) of the patients. DISCUSSION: The meta-analysis will retrospectively examine current evidence regarding the effectiveness of the practice of acupuncture combined with herbal medicine to treat plaque psoriasis. This study may reveal, for the first time, an adjuvant therapy for psoriasis. TRIAL REGISTRATION: As the study is a systematic review protocol, trial registration will not be necessary. An article containing the results will be published in a peer-reviewed journal and disseminated through scientific conferences.